ANALISIS VOLUME LALU LINTAS JALAN RAYA MASTRIP SURABAYA—JALAN RAYA BAMBE KABUPATEN GRESIK - Aditya Pratama; Teki Tjendani , Hanie (Jurnal Rekayasa Teknik Sipil dan Lingkungan - CENTECH, 2024)
Mastrip Highway – Bambe Highway, Gresik Regency is included in the UD 2/2 road type where the two lanes are not limited by the road median so that each lane direction is close to each other which has a length of 2.8 km with a lane width of 4 meters and the number of lanes is 2 lanes, with the width of the right and left side shoulders is 0.8 meters. Referring to the density of traffic flow, side obstacles and degrees of saturation on the Mastrip Highway - Bambe Highway section of Gresik Regency, it is necessary to analyze the performance of road and traffic sections using manual count on this road section. The use of the method in this study is quantitatively with the approach of the 2023 Indonesian Road Capacity Guidelines (PKJI). Data acquisition comes from primary data and secondary data. Primary Data is data from traffic surveys that have been conducted in the field on the Mastrip Surabaya - Bambe Highway, Gresik Regency. The results of the analysis show that the peak hours of traffic flow volume occur on Tuesday, January 16, 2024 at 16.00 – 17.00 with a total of 1,800.2 skr / hour.